Limited fluoroscopy catheter ablation of accessory pathways in children. Issue 4 (October 2017) - Swissa, Moshe; Birk, Einat; Dagan, Tamir; Abby Naimer, Sody; Fogelman, Michal; Einbinder, Tom; Bruckheimer, Elchanan; Fogelman, Rami
Abstract: Background: Limited fluoroscopy ablation using 3D electro-anatomical system (3DS) has been used for arrhythmias in children, however it is not a common practice. We aimed to facilitate a fluoroscopy limited approach for ablation of accessory pathways (AP) in children. Methods: Following electrophysiologic (EP) catheter placement a single dual-plane fluoroscopic image (right anterior oblique-30° and left anterior oblique-60° views) was acquired and the 3DS views were rotated to be a perfect match to the fluoroscopy. Ninety-four consecutive pediatric patients [mean age 11.8 ± 4.1 (4.2–18) years, 61.7% males] with Wolf–Parkinson–White syndrome underwent ablation of an AP. Fifty-seven had manifest AP, 54 had left-sided AP (LSAP) and 40 had right-sided AP (RSAP). Results: The acute success rate was 95.7% (90/94), with a recurrence rate of 1.1% (1/90) at a mean follow-up of 13 ± 5.5 (4.4–22.9) months. Mean procedure and fluoroscopy times were 144 ± 45 (55–262) min and 1.8 ± 1.4 (0.1–5.6) min, respectively. Comparison of the first 20 procedures to the next 74 procedures demonstrated an extended procedure time (171 ± 53 min vs 135 ± 38 min, p < 0.005), however the fluoroscopy time, the number of long applications, the time to effect, and the acute success rate were similar. There were no permanent ablation-related complications. Conclusions: A limited fluoroscopy approach for ablation of AP in children using 3DS is easily acquired, adapted, reduces the fluoroscopy time, and has an excellent efficacy and safety profile.